Ocular Inflammation in Neurorheumatic Disease - Vodopivec, Ivana; Lobo, Ann-Marie; Prasad, Sashank (Seminars in Neurology, 2014)
Neuroimmunologic and systemic rheumatic diseases are frequently accompanied by inflammation of the eye, ocular adnexa, and orbital tissues. An understanding of the diverse forms of ophthalmic pathology in these conditions aids the clinician in making appropriate preventative, diagnostic, therapeutic, and prognostic decisions. In this review, the authors address ocular inflammation in neurorheumatic disease in three sections: first, they highlight current perspectives on immune mechanisms in the development of these disorders; next, they provide a framework for the recognition and evaluation of ophthalmologic inflammatory entities; finally, they discuss in detail several inflammatory conditions that affect the nervous system and the eye, emphasizing the features that should alert neurologists to initiate ophthalmologic evaluation. The conditions discussed include multiple sclerosis, neuromyelitis optica, chronic relapsing inflammatory optic neuropathy, Susac syndrome, Cogan syndrome, acute posterior multifocal placoid pigment epitheliopathy, Vogt-Koyanagi-Harada disease, Behçet disease, sarcoidosis, systemic lupus erythematosus, granulomatosis with polyangiitis (Wegener granulomatosis), polyarteritis nodosa, giant cell arteritis, IgG4-related disease, and Sjögren syndrome.
Keywords: nervous system; neuroimmunology; neuroinflammation; ocular inflammation; uveomeningeal syndromes